In-Vitro Comparison of Primary Setting Time and Surface Porosity of Two Types of Mineral Trioxide Aggregate (MTA) - Sepideh Banava; Zohreh Janfeshan; Mohammad ali Saghiri (Islamic Dental Association of Iran, 2013)
Background and Aim : There are disadvantages in using MTA, such as the extended setting time and the difficulty in its manipulation. The aim of this in vitro study was to compare the primary setting time and surface porosity of two commercial brands of tooth colored MTA .   Materials and Methods : In this experimental study two brands of MTA were evaluated Group1: ProRoot MTA (Dentsply, USA), and group 2: Angelus MTA (Angelus, Brazil). Five samples of each material were prepared and evaluated for primary setting time with a Gilmore needle according to ISO 6876: 2001 with a cylindrical stainless steel mold (10mm×1mm) in an incubator with 37±1 degrees centigrade and relative humidity of over 95%. Specimens were prepared and observed under a scanning electron microscope (SEM) for surface porosity. Data were analyzed with T-test .   Results : Primary setting time of the materials were 38.72±0.61 and 22.46 ± 0.61 ProRoot and Angelus MTA, respectively. Statistical analysis revealed that the differences between setting times of the materials were significant (p<0.001). ProRoot MTA showed better surface characterization compared with Angelus MTA.   Conclusion : The primary setting time of Angelus MTA was lower than that of ProRoot MTA but the surface characterization (topography and porosity) of ProRoot MTA was better than that of Angelus MTA after final setting time.